Otitis media from the perspective of family psychician and pediatrician - Ścińska, Anna; Kukwa, Wojciech; Jeżewska, Elżbieta; Kukwa, Andrzej (Przewodnik Lekarza/Guide for GPs, 2006)
Authors present basic information on diagnosis and management of otitis media. Acute and chronic otitis media as well as otitis media with effusion has been addressed from the perspective of family physicians and pediatricians.